A comparative evaluation between median and paramedian approaches for sub-arachnoid block in elderly patients - Singh, Pooja; Agrawal, Subhash K.; Dwivedi, Sudhakar; Yadav, Avtar (International Journal of Research in Medical Sciences, 2017)
Background: Spinal anaesthesia in elderly patients is frequently associated with significant technical difficulties. Spinal anaesthesia can be given by either paramedian or median approach. Paramedian approach has been used as an alternative in case of failure with median approach. The goal of this study is to determine which of these two approaches should be preferred as a first choice of spinal anaesthesia in elderly patients. Methods: The study included 100 patients of either sex, aged 50 years and above, who received spinal anaesthesia either with the midline approach (group M, n=50) or paramedian approach (group PM, n=50). Results: The success rate of paramedian group was 100% as compared to 96 % in median group. The first attempt success rate was 90% in group PM and 70% in group M. Paraesthesia was felt in 5 patients (10%) in midline group and in 2 patients (4%) in paramedian group. Hemorrhagic tap was seen in 2 patients each in both the groups . None of the patients in Group M had postdural puncture headache (PDPH) as opposed to 2 patients in Group M. Conclusions: Thus the study conclude that paramedian approach is a better approach for spinal anaesthesia in elderly patients in terms of success rate, success at first attempt, complications like paraesthesia, PDPH and failure of sub-arachnoid block. Thus study recommends the routine use of paramedian approach for sub-arachnoid block in elderly patients as first choice.